Red Chinese Battleplan (United States, 1960)
China 1900-1960. When this documentary was made in 1960 American anticommunism was strong. During the Korean War Chinese communist soldiers had fought and killed 50,000 Americans. This documentary does an excellent job of depicting the horrors of Chinese communism and its insidious dissemination by secret agents. It is a leading contender for the title of the most anti-communist film ever made about the Red Menace!
Keywords: Documentary films